The Role of Perceived Benefits, Installations, and Government Initiatives in Influencing Solar Energy Adoption Intentions at the Household Level in Jakarta - Emmanuel, Jovan; Gabriel, Djoko Sihono (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study investigates the factors that influence the intention to adopt solar energy at the household level in Jakarta. As urban energy demands increase and environmental concerns intensify, renewable energy technologies, particularly solar power, offer a sustainable alternative. The research primarily focuses on three key drivers: perceived benefits, installation-related aspects, and the role of government initiatives. Using a structured survey questionnaire, data were gathered from residents across various housing areas in Jakarta. The questionnaire assessed respondents’ awareness of renewable energy, perceptions of its advantages, perceived ease or complexity of installation, and the impact of governmental policies or incentives. The results of the analysis indicate that perceived benefits—such as long-term cost savings and environmental advantages—have a strong and statistically significant effect on adoption intentions. Government initiatives, including subsidies, public campaigns, and regulatory support, also play a critical role in shaping household decisions. Installation factors, although slightly less influential, still contribute meaningfully, particularly in terms of ease of access to reliable installation services and associated upfront costs. These findings highlight the importance of a multi-faceted approach to increasing residential solar energy adoption. Specifically, they underscore the need for government efforts to enhance public awareness and provide financial incentives, as well as the importance of ensuring accessible and user-friendly installation processes. The insights from this study can inform energy policymakers, private sector stakeholders, and urban planners in crafting effective strategies that support a greener and more sustainable urban energy landscape in Jakarta.